Effect of Tizanidine on Spasticity in Pediatric Patients with Cerebral Palsy: A Systematic Review - Anna Dominique Py Castro; Maria Antonia Aurora Moral Valencia (Korean Child Neurology Society, 2023)
Purpose Cerebral palsy (CP) is a permanent, non-progressive disorder of the developing brain. Tizanidine is an effective treatment for spastic CP; however, insufficient evidence exists regarding its effect on motor function and side-effect profile. This review explored the effects and safety of tizanidine in treating spasticity among pediatric patients with CP. Methods Two reviewers conducted a literature search. The Cochrane risk of bias tool and the 14-item National Institutes of Health Quality Assessment Tool were used to evaluate the risk of bias. A systematic review was performed for relevant studies. Results Five studies were included: three randomized controlled trials (RCTs) and two observational studies. The control group received a placebo in two RCTs, while baclofen was used in the remaining studies. Tizanidine dosage and duration varied across reports, except for the two observational studies. Excepting one observational study, tizanidine was associated with a greater improvement on the modified Ashworth scale. Pain reduction was also greater with tizanidine treatment compared to the placebo, as evidenced by one RCT. Three studies evaluating gross motor function reported superior results with tizanidine compared to baclofen. Two RCTs indicated similar safety profiles between tizanidine and the placebo. The remaining studies reported a more favorable safety profile for tizanidine than baclofen. Conclusion The studies examined in this review reported beneficial effects of tizanidine on spasticity, pain, and gross motor function. Tizanidine usage was associated with no serious adverse events, reflecting a better safety profile than baclofen. Nevertheless, high-quality RCTs are recommended to support tizanidine administration in pediatric patients.